Patient Selection in Deep Brain Stimulation: A Role for Transcranial Direct Current Stimulation to Enhance the Levodopa Challenge? - Lukas L. Goede; Patricia Zvarova; Bahne H. Bahners; Andreas Horn (Annals of Clinical and Translational Neurology)
ABSTRACT Dopaminergic medication and deep brain stimulation (DBS) improve motor symptoms in Parkinson's disease (PD), but levodopa response alone may not predict DBS outcomes. We retrospectively analyzed 19 PD patients undergoing levodopa challenges with and without prior transcranial direct current stimulation targeting a defined PD response network. Levodopa improved motor performance more after tDCS than sham (41.72% vs. 31.52%; p < 0.001). In ten patients who later received DBS, the combined levodopa‐tDCS response accounted for DBS outcomes (p = 0.02). These findings suggest that targeted tDCS enhances levodopa effects and may be of potential use to optimize DBS candidate selection.